Studying marcomolecular transitions by NMR and computer simulations - Stelzl, LS (2014)
Macromolecular transitions such as conformational changes and protein-protein association underlie many biological processes. Conformational changes in the N-terminal domain of the transmembrane protein DsbD (nDsbD) were studied by NMR and molecular dynamics (MD) simulations. nDsbD supplies reductant to biosynthetic pathways in the oxidising periplasm of Gram-negative bacteria after receiving reductant from the C-terminal domain of DsbD (cDsbD). Reductant transfer in the DsbD pathway happens via protein-protein association and subsequent thiol-disulphide exchange reactions. The cap loop shields the active-site cysteines in nDsbD from non-cognate oxidation, but needs to open when nDsbD bind its interaction partners. The loop was rigid in MD simulations of reduced nDsbD. More complicated dynamics were observed for oxidised nDsbD, as the disulphide bond introduces frustration which led to loop opening in some trajectories. The simulations of oxidised and reduced nDsbD agreed well with previous NMR spin-relaxation and residual dipolar coupling measurements as well as chemical shift-based torsion angle predictions. NMR relaxation dispersion experiments revealed that the cap loop of oxidised nDsbD exchanges between a major and a minor conformation. The differences in their conformational dynamics may explain why oxidised nDsbD binds its physiological partner cDsbD much tighter than reduced nDsbD. The redox-state dependent interaction between cDsbD and nDsbD is thought to enhance turnover. NMR relaxation dispersion experiments gave insight into the kinetics of the redox-state dependent interaction. MD simulations identified dynamic encounter complexes in the association of nDsbD with cDsbD. The mechanism of the conformational changes in the transport cycle of LacY were also investigated. LacY switches between periplasmic open and cytoplasmic open conformations to transport sugars across the cell membrane. Two mechanisms have been proposed for the conformational change, a rocker-switch mechanism based on rigid body motions and an “airlock” like mechanism in which the transporter would switch conformation via a fully occluded structure. In MD simulations using the novel dynamics importance sampling approach such a fully occluded structure was found. The simulations argued against a strict “rocker-switch” mechanism.